2016
DOI: 10.1104/pp.16.00393
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chromatin Regulators Reveals Specific Features of Rice DNA Methylation Pathways

Abstract: Plant DNA methylation that occurs at CG, CHG, and CHH sites (H = A, C, or T) is a hallmark of the repression of repetitive sequences and transposable elements (TEs). The rice (Oryza sativa) genome contains about 40% repetitive sequence and TEs and displays specific patterns of genome-wide DNA methylation. The mechanism responsible for the specific methylation patterns is unclear. Here, we analyzed the function of OsDDM1 (Deficient in DNA Methylation 1) and OsDRM2 (Deficient in DNA Methylation 1) in genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
157
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(178 citation statements)
references
References 58 publications
21
157
0
Order By: Relevance
“…In contrast, in maize the levels of m CHG and m CHH were affected more strongly than those of m CG. Our results are similar to the data from the rice ddm1 mutation, which mostly affects m CHG levels (Tan et al ). These observations suggest that DDM1 has different effects on DNA methylation patterns in diverse species.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, in maize the levels of m CHG and m CHH were affected more strongly than those of m CG. Our results are similar to the data from the rice ddm1 mutation, which mostly affects m CHG levels (Tan et al ). These observations suggest that DDM1 has different effects on DNA methylation patterns in diverse species.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it was thought that DDM1 facilitates CMT2 ‐mediated CHH methylation independently of the RdDM pathway (Zemach et al ). However, a recent study in rice has indicated that OsDDM1 may be involved in RdDM‐mediated m CHH methylation at genic regions (Tan et al ). Thus, whether DDM1 participate in RdDM pathway may vary among plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The genome-wide DNA methylation level is reduced to 17% in Osdrm2 compared to the WT and the RdDM pathway is deficient. In contrast to Arabidopsis, OsDRM2 is the major CHH MET in rice [46]. Heterologous expression of OsDRM2 in yeast confirmed that OsDRM2 could methylate DNA de novo [48].…”
Section: Main Regulators Of Dna Methylation In Ricementioning
confidence: 95%
“…These two genes share 93% similarity and their expression patterns are also similar. Interestingly, only the double mutants Osddm1a and Osddm1b show severe developmental defaults and a complete sterility, suggesting functional redundancy [46,47]. The global DNA methylation level is reduced by 54% in the double mutant Osddm1a Osddm1b compared to the WT.…”
Section: Main Regulators Of Dna Methylation In Ricementioning
confidence: 98%
See 1 more Smart Citation